Prǣrūp watthanatham čhittakam rūam samai Vīatnām = Cultural representation in transition, new Vietnamese painting' . - Siam Society ([Bangkok] Sayām Samākhom 147 pages, 1996)
Reproduction of modern painting by 20 Vietnamese artists; includes their bio-datas.
Thai, English, and Vietnamese.
Keywords: Painting, Vietnamese -- 20th century -- Exhibitions